2010
DOI: 10.1007/978-3-642-13443-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Propentofylline: Glial Modulation, Neuroprotection, and Alleviation of Chronic Pain

Abstract: Propentofylline is a unique methylxanthine with clear cyclic AMP, phosphodiesterase, and adenosine actions, including enhanced synaptic adenosine signaling. Both in vitro and in vivo studies have demonstrated profound neuroprotective, antiproliferative, and anti-inflammatory effects of propentofylline. Propentofylline has shown efficacy in preclinical models of stroke, opioid tolerance, and acute and chronic pain. Clinically, propentofylline has shown efficacy in degenerative and vascular dementia, and as a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…The realization of new players in opioid analgesia is a major development in opioid pharmacology and thus has been the focus of several excellent recent reviews (Mika, 2008;Romero-Sandoval et al, 2008;Ueda and Ueda, 2009;Watkins et al, 2009;Ji, 2010;O'Callaghan and Miller, 2010;White and Wilson, 2010;Sweitzer and De Leo, 2011). Here, we will highlight and extend previous reviews to discuss the evidence that acute opioid analgesia is substantially modified by the rapid opioid-induced initiation of central immune signaling and that upon repeated opioid exposure, continued central immune signaling leads to analgesic tolerance and enhanced pain states.…”
Section: What Is the Impact Of Proinflammatory Central Immune Signmentioning
confidence: 99%
“…The realization of new players in opioid analgesia is a major development in opioid pharmacology and thus has been the focus of several excellent recent reviews (Mika, 2008;Romero-Sandoval et al, 2008;Ueda and Ueda, 2009;Watkins et al, 2009;Ji, 2010;O'Callaghan and Miller, 2010;White and Wilson, 2010;Sweitzer and De Leo, 2011). Here, we will highlight and extend previous reviews to discuss the evidence that acute opioid analgesia is substantially modified by the rapid opioid-induced initiation of central immune signaling and that upon repeated opioid exposure, continued central immune signaling leads to analgesic tolerance and enhanced pain states.…”
Section: What Is the Impact Of Proinflammatory Central Immune Signmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that propentofylline [PPF, 3-methyl-1-(5'-oxohexyl)-7-propylxanthine], a xanthine derivative, presents profound neuroprotective, antioxidant and anti-inflammatory effects (16,17). Clinically it has shown efficacy in degenerative vascular dementia (18) and as a potential adjuvant treatment to Alzheimer's disease (19,20), schizophrenia (21) and multiple sclerosis (22).…”
mentioning
confidence: 99%
“…Clinically it has shown efficacy in degenerative vascular dementia (18) and as a potential adjuvant treatment to Alzheimer's disease (19,20), schizophrenia (21) and multiple sclerosis (22). PPF probably depresses activation of microglial cells and astrocytes, which is associated with neuronal damage during inflammation and hypoxia and consequently decreases glial production and release of damaging proinflammatory factors (16). In the EB demyelinating Arch Endocrinol Metab.…”
mentioning
confidence: 99%
“…Propentofylline [PPF, 3-methyl-1-(5´-oxohexyl)-7-propylxanthine] is a xanthine derivative with pharmacological effects distinct from those of the classical methylxanthines theophylline and caffeine 4 . In vitro and in vivo studies have demonstrated extensive neuroprotective, antiproliferative and anti-inflammatory effects of PPF in several experimental models in animals 4 .…”
mentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated extensive neuroprotective, antiproliferative and anti-inflammatory effects of PPF in several experimental models in animals 4 . It was sucessfully used in degenerative vascular dementia and as a potential adjuvant treatment to Alzheimer's disease, schizophrenia and multiple sclerosis 4 .…”
mentioning
confidence: 99%